Perancangan Mesin Pembersih Pipa dari Oli Anticorit di PT. SPINDO Unit 6 - Fitkirana, Edwin; Arizal, Heru (Universitas Nusantara PGRI Kediri, 2022)
PT. Steel Pipe Industry of Indonesia, Tbk. (SPINDO) is one of the industries engaged in the manufacture of steel pipes for various needs, ranging from furniture, construction, automotive, etc. In the process of making steel pipes, there is a special treatment to slow down the corrosion rate, one of which is by dipping the pipe into anticorit oil. Some of the customers asked for special treatment on the galvanized iron square pipe to be cleaned of anticoritic oil. The problems that occur in PT. SPINDO unit 6, namely the process of cleaning pipes from anti-rust oil is still carried out by wiping the pipe surface so it takes a long time, which is 30 seconds/pipe. The purpose of this design is to determine the components, engine working mechanisms, and designs used in pipe cleaning machines from anticorit oil. With this design, it is hoped that it can become an illustration in the manufacture of anticorit oil pipes for cleaning machines for the speed up process.